(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This research delves into the critical area of raising awareness about child sexual abuse within society. With a focus on shedding light on this pervasive issue, the study examines the prevalence and impact of child sexual abuse, particularly within the context of societal attitudes and responses. By exploring the challenges and complexities inherent in addressing this sensitive topic, the research aims to contribute to the broader discourse on safeguarding children and fostering a culture of accountability and protection. Through empirical investigation and analysis, this study seeks to provide insights into effective strategies for increasing awareness and combating child sexual abuse, ultimately advocating for the well-being and safety of vulnerable children in our communities.